Analysis of mechanical failures after anatomic acromioclavicular joint reconstruction. Issue 5 (September 2015) - Biggers, Marcus D.; Mascioli, Anthony A.; Mauck, Benjamin M.; Azar, Frederick M.; Smith, Richard A.; Throckmorton, Thomas W.
<x xml:space="preserve">Abstract</x> Background: We analyzed a series of anatomic acromioclavicular joint reconstructions to identify risk factors that may predict failure. We hypothesized there would be no difference in failure rates relative to any of these variables. Methods: A consecutive series of 43 patients who had anatomic acromioclavicular joint reconstruction between 2007 and 2013 were identified. Failure was defined as loss of reduction with concomitant pain, dysfunction requiring revision surgery, or both. Injury characteristics, surgical techniques, and patient factors were recorded. Results: Three patients required further surgery for infection or late traumatic failure and were not included in the analysis of mechanical failures. Six patients (15%) had revision because of failed reconstruction with pain. None of the patient demographic factors were associated with failure. The failure rate was significantly lower in patients in whom interference screws were used for graft fixation (7% vs. 44%, P=0.016) and in those who had concomitant distal clavicular excision (9% vs. 60%, P=0.018). Reconstructions with nonbiologic fixation in addition to the tendon graft also trended toward lower failure rates (9% vs. 43%, P=0.055). The failure rate was lower in type III injuries (10%) than type V injuries (22%), but this difference did not reach statistical significance because of the small size of the group that required reoperation. Conclusion: Anatomic acromioclavicular joint reconstruction resulted in a 15% mechanical failure rate in this series. Statistical analysis of 14 factors found that the use of interference screw fixation and concomitant distal clavicular excision were statistically significant protective factors against failure.